The effect of brain-breaks on physical activity level, physical activity motivation and cognitive functions among the medical students at Universiti Sains Malaysia - Rahmat, Ainul Shazmira (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
This study aimed to examine the effect of brain-breaks intervention on physical activity level, decisional balance, self-efficacy and cognitive functions among the medical students of Universiti Sains Malaysia. In the present study, twenty participants (age: 22.47 ± 1.22 years old) were recruited for this study, and they completed two cognitive tests and three questionnaires at pre- and post- intervention. The cognitive test includes the Reaction Time Test and Stroop Test, which are used to measure the response time, mental attentional vitality and flexibility. The questionnaires used include Decisional Balance, Self-Efficacy and also Leisure Time Exercise questionnaire (LTEQ). The participants were randomly assigned to two groups: 1) control, and 2) Intervention. The intervention period was three weeks of brain breaks videos. After completing the intervention phase, the result show that the intervention group have significant result on response time (p = 0.002) and attentional mental vitality and flexibility (p = 0.011). Also, significant increase in decisional (p = 0.0018). The physical activity level of the participants in both groups also shows increment, where the number of sedentary participants decreasing and the number of active participants increasing. In conclusion, the brain-breaks intervention has a positive effect on cognitive functions, physical activity motivation and physical activity level among the medical students at Universiti Sains Malaysia.